Vesta and Ceres insights from the Dawn Mission for the origin of the solar system - Marchi, Simone; Raymond, Carol A.; Russell, C. T. (Cambridge University Press, 2022)
The NASA Dawn mission, launched in 2007, aimed to visit two of the most massive protoplanets of the main asteroid belt: Vesta and Ceres. The aim was to further our understanding of the earliest days of the Solar System, and compare the two bodies to better understand their formation and evolution. This book summarises state-of-the-art results from the mission, and discusses the implications for our understanding not only of the asteroid belt but the entire Solar System. It comprises of three parts: Part 1 provides an overview of the main belt asteroids and provides an introduction to the Dawn mission; Part 2 presents key findings from the mission; and Part 3 discusses how these findings provide insights into the formation and evolution of the Solar System. This is a definitive reference for academic researchers and professionals of planetary science, asteroid science and space exploration.
Keywords: Dawn Mission (U.S.); Ceres (Dwarf planet); Vesta (Asteroid)